P230 A retrospective database study of persistence and adherence in patients with asthma in the UK (UK-THIN): fluticasone furoate/vilanterol (FF/VI) versus budesonide/formoterol (BUD/FM). (12th November 2019) - Svedsater, H; Parimi, M; Ann, Q; Gray, CM; Nixon, M; Boxall, N
Abstract : Introduction and objectives: A retrospective cohort analysis was conducted comparing persistence with, and adherence to, different inhaled corticosteroid/long-acting-β2 -agonist (ICS/LABA) treatments by asthma patients. Here we report findings from patients initiating treatment with either FF/VI or BUD/FM, the latter administered either as flexible or fixed-dose. Methods: Patients in the UK with data registered in The Health Improvement Network (THIN) database, who had a first prescription (index date) for any ICS/LABA between 1 January 2013–17 January 2018 (study period) and a prior asthma diagnosis, were included if they had ≥12 months medical history prior to index date plus ≥1 post-index ICS/LABA prescription. Patients were excluded if aged <12 years or if there were records for either COPD diagnosis or previous non–study ICS/LABA treatment prior to index date. Study cohorts were matched by propensity score (1:up to 4; greedy method). Primary objective was to compare persistence of comparator ICS/LABAs up to 12 months post-index treatment (time to discontinuation* including switch). Secondary objectives were: proportion of days covered (PDC) and proportion of patients with ≥50% and ≥80% PDC at 12 months post-index; and rescue use (annualised number of short-acting bronchodilator prescriptions/patient) within 12 months after treatment initiation. Results: A total of 937 patients initiating FF/VI were matched to 3232 patients initiating BUD/FM. A higher proportion of patients persisted with FF/VI versus BUD/FM over 12 months (Kaplan-Meier analysis; Figure ). The likelihood of discontinuing treatment within 12 months after initiation was 35% lower for FF/VI than BUD/FM (index year-adjusted, hazard ratio=0.65; 95% CI 0.56–0.75; p<0.001). Median (interquartile range) PDC was 88.2 (61.4–100.0) for FF/VI and 77.7 (50.7–100.0) for BUD/FM (p<0.0001), with significantly higher odds of achieving ≥50% and ≥80% PDC for FF/VI versus BUD/FM (779/936 [83.2%] vs 2447/3232 [75.7%]; odds ratio=1.35; 95% CI 1.09–1.67; p=0.006 and 544/936 [58.1%] vs 1562/3232 [48.3%]; odds ratio=1.28; 95% CI 1.08–1.52; p=0.004, respectively; per-protocol analyses). Annualised rescue use was numerically higher for FF/VI (9.3) versus BUD/FM (5.9). Conclusion: UK asthma patients initiating FF/VI were more likely to have higher persistence and better adherence to treatment than those initiating BUD/FM. GlaxoSmithKline plc. -funded study (209967/HO-18–19688).